QUANTITATIVE ESTIMATIONS OF POLYPHENOLIC COMPOUNDS IN VICIA FABA L. (LEGUMINOSAE) SEEDS (Sciences & Technologie. C, Biotechnologies, 2002)
Polyphenolic compounds and tannins are natural substances of secondary plant metabolism. They are well known for their antinutritional effects. These properties are due to their ability to interact and precipitate protein of the diet. They are responsible for the inhibition of digestion and the decrease of nutritive value of some legumes and  cereals grains. Owing to their ability to interact strongly with protein of the ratio, they could be responsible to the inhibition activity of several enzymes [1,2]. So an important particularity must be reserved to these compounds when they are integrated into the diet. Five methods for the  measurement of total phenolics, condensed tannins, and tanning capacity of Vicia faba L.  were  tested  for  their  reliability ; some  of  them  were  improved  for  their  sensitivity.  The results  were interpreted  so  as  to  draw the phenolic pattern  of each  variety  of Vicia faba L, and they revealed different cases.